Media Literacy Based Android Application to Introduce Sumbawa Culture for Visual Disabilities - Shinta Esabella; Nora Dery Sofya; Erwin Mardinata; Muhammad Hidayatullah; Titi Andriani; Gunawan (Postgraduate, University of Mataram, 2023)
This research aims to introduce Sumbawa culture to blind disability based android smartphone applications that can utilize feature reader screens and barcodes on objects historical. Output from application This is information in the form of audio details of cultural sites in the Inner Palace Loka, Bala Kuning Palace, Bala Puti Palace, Bala Datu Ranga, and the Sumbawa Museum. This research is quantitative method with build uses waterfall method and design with UML models with test six aspect appropriateness to application. The resulting average value for the attractiveness p ax is 1.90 and the average score for as a perspicuity peak of 1.77. Third aspect from UEQ, efficiency value with an average of 1.61 and dependability aspects with value 1.55. Whereas the stimulation aspect on the UEQ model is 1.49 and the novelty aspect with the average value is 1.39. From testing aspect perspicuity, efficiency, dependability, stimulation and novelty show quality application are excellent. Whereas the attractiveness aspect generates very good value. Application literacy culture for blind disability is something effort in preserving culture and can be accessible on google play store.